Reorienting Bloom’s Taxonomy: Toward a Tawhid-Based Paradigm of Islamic Educational Evaluation - Yusron Nur Hadi; Nurul Laely Mahmudah; Shodiq Abdullah; Agus Sutiyono; Karnadi Hasan (Journal of Indonesian Islamic Studies, 2025)
The widespread use of Bloom’s Taxonomy in Islamic Religious Education (IRE) evaluation provides a systematic framework for measuring cognitive, affective, and psychomotor learning outcomes. However, its application remains predominantly oriented toward measurable competencies and does not fully represent the spiritual and moral dimensions that constitute the broader aims of Islamic education. This study aims to critically examine the limitations of Bloom’s Taxonomy in IRE evaluation and reconstruct its paradigm based on tawhid as the fundamental orientation of educational evaluation. In this reconstruction, tawhid is understood not merely as a dimension of faith, but as an epistemological and axiological foundation that integrates knowledge, values, practice, and character within a unified conception of human development. This study employs a qualitative approach using library research. Data were obtained from relevant scholarly literature on Bloom’s Taxonomy, educational assessment, Islamic Religious Education, Islamic educational objectives, and value-based education, supplemented by the Qur’an and Hadith as normative sources. Data were analyzed through content analysis involving reduction, categorization, comparison, interpretation, and conceptual synthesis. The findings indicate that the main limitation of Bloom’s Taxonomy does not lie in its cognitive, affective, and psychomotor domains, but in the tendency to position competency attainment as the endpoint of evaluation. From a tawhid perspective, educational evaluation should integrate intellectual, spiritual, moral, and practical dimensions within a unified framework. The proposed reconstruction repositions iman (faith) as the orienting foundation, ‘ilm (knowledge) as the epistemic basis, internalization of values as the affective process, ‘amal (practice) as the actualization of learning, and akhlak (character) as the integrative manifestation of educational transformation. Tawhid thus functions as the unifying principle connecting knowledge, belief, internalization, practice, and character formation. This reconstruction shifts IRE evaluation from competency measurement toward holistic personality transformation while retaining the pedagogical strengths of Bloom’s Taxonomy.